Sign Communication in Different Languages - Abduzuhurovna, Abduazizova Durdona (International Journal of Human Computing Studies, 2022)
The relevance of the article is due to the change in the scientific paradigms of modern linguistics, which has significantly increased the relevance of research on nonverbal communication, in particular, sign communication. The article examines and conducts a typological analysis of kinetic means in multi-system languages, parakinesic means that differ in their functions are considered and their classification is given. When comparing gestures, facial expressions and body movements, the author is based on their form (kinesic), meaning and distribution; the nature, meaning, and functions of paralinguistic means in communication are studied; issues of incorrect interpretation of gesture semantics are touched upon, which can subsequently lead to significant errors in formal communication in international communication. The study of the interaction of verbal and nonverbal means reveals certain patterns in the coordination of certain gestures and different parts of speech, gestures and syntactic of statements; the processes of a kind of mutual enrichment of verbal and nonverbal units are interesting — all this is included in the linguistic aspect studied by the author of the problem. The language and its accompanying kinesic and phonation gestures have a pronounced national characteristic and are associated with an ethnic, geographical, professional, socio-cultural environment. Paralinguistic means appear to be universal in their presence, but in their image, different peoples differ in their national and cultural characteristics. The author establishes that the communicative unit in the connected functioning of verbal and nonverbal signs is a verbal utterance, in which nonverbal signs act as communicative components that concretize semantic, evaluative and social information.